2023
DOI: 10.3389/fpsyg.2023.1114816
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rapid weight loss on mood states and burnout of Brazilian jiu-jitsu athletes during a competitive process

Abstract: The current study aimed to analyze the psychological alterations resulting from rapid weight loss in the mood states and burnout of male Brazilian jiu-jitsu athletes. For the purpose of this study, 31 Brazilian jiu-jitsu athletes participated, divided into two groups (RWLG: rapid weight loss group and CG: control group). Data collections were performed at three moments (1: baseline, before weight loss; 2: weigh-in, during the official competition; and 3: recovery, 7 to 10 days after the competition), with appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Nevertheless, the POMS has shown utility in screening for mental health issues [ 6 ] and predictive effectiveness in competitive domains including sports, where negative moods can hinder performance [ 1 , 2 ]. The BRUMS has often been used to predict sports performance, and also to assess athletes’ mood responses to various situational stressors, such as training load, underperformance, injury [ 18 ], poor sleep quality [ 19 ], rapid weight loss [ 20 , 21 ], and restricted food and drink intake during Ramadan [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the POMS has shown utility in screening for mental health issues [ 6 ] and predictive effectiveness in competitive domains including sports, where negative moods can hinder performance [ 1 , 2 ]. The BRUMS has often been used to predict sports performance, and also to assess athletes’ mood responses to various situational stressors, such as training load, underperformance, injury [ 18 ], poor sleep quality [ 19 ], rapid weight loss [ 20 , 21 ], and restricted food and drink intake during Ramadan [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…This instrument has 24 question items from six negative mood state subscales: (i) anger, (ii) confusion, (iii) depression, (iv) fatigue, (v) tension and (vi) vigor. One positive mood subscale: (i) enthusiasm [23]. Responses were assessed with a Likert scale from 1 to 5 [47].…”
Section: Assessment Msmentioning
confidence: 99%
“…MS has an important role for studentathletes in following the PE process optimally in the long term, because positive MS has the potential to reduce levels of burnout, depression [16], stress [17,18], anger [19], on the other hand studentathletes with negative MS tend to have a low level of involvement in learning activities [20,21,22]. A previous study has confirmed that the benefits of MS can trigger enthusiasm in studentathletes to achieve a goal in the context of physical education [23], or sports [24]. Research by Legey et al [25], reported that positive MS can help student athletes more active in physical activity.…”
Section: Introductionmentioning
confidence: 99%